Kaempferol restores the susceptibility of ESBLs Escherichia coli to Ceftiofur - Li, Peng-Cheng; Tong, Yin-Chao; Xiao, Xing-Lan; Fan, Yun-Peng; Ma, Wu-Ren; Liu, Ying-Qiu; Zhuang, Shen; Qing, Su-Zhu; Zhang, Wei-Min (Frontiers in Microbiology, 2024)
IntroductionThe development of extended-spectrum-beta-lactamase (ESBLs) Escherichia coli (E. coli) has become a global threat to public health. An alternative strategy to alleviate this is identifying potential natural compounds to restore antibiotic activity against ESBLs E. coli. This study aimed to find a possible compound to restore ESBLs E. coli sensitivity to ceftiofur.MethodsThe synergistic effect of kaempferol and ceftiofur against ESBLs E. coli was investigated by checkerboard assays, time-kill, growth curves, and scanning electronic microscope. The impact of kaempferol with ceftiofur on the biofilm of ESBLs E. coli was evaluated by crystal violet staining and laser scanning confocal microscopy and this study also assessed the effect of kaempferol on the initial adhesion and aggregation of E. coli (SY20) by examining motility, adhesion, and surface characteristics. The RT-qPCR was used to determine the effect of kaempferol on the expression of genes related to the LuxS/AI-2 quorum sensing system in ESBLs E. coli, and the effect of kaempferol on AI-2 signaling molecules was determined by molecular docking and bioassay. The impact of kaempferol on the activity of blaCTX-M-27 protein was determined by RT-qPCR, molecular docking, and nitrofen experiments, the results were further verified by transcriptome analysis. The mouse infection model was established, and the inhibitory mechanism of kaempferol with ceftiofur on bacteria in vivo was further verified by HE staining and immunohistochemistry.Results and discussionKaempferol with ceftiofur exerts synergistic antibacterial and bactericidal effects on ESBLs E. coli by influencing β-lactamase activity, biofilm formation, and LuxS/AI-2 QS system. In vivo, kaempferol protected the small intestinal villi from the damage of ESBLs E. coli. Furthermore, kaempferol fully restores the activity of ceftiofur in animal infection models by relieving the TLR4/NF-κb pathway. In conclusion, the sensitivity of ESBLs E. coli to ceftiofur in vitro and in vivo could be enhanced by kaempferol, which showed that kaempferol may be a kind of antibiotic adjuvant.